Corrosion behavior of dental alloys used for retention elements in prosthodontics. (9th April 2016) - Nierlich, Judith; Papageorgiou, Spyridon N.; Bourauel, Christoph; Hültenschmidt, Robert; Bayer, Stefan; Stark, Helmut; Keilig, Ludger
Abstract : The purpose of this study was to investigate the corrosion behavior of 10 different high noble gold‐based dental alloys, used for prosthodontic retention elements, according to ISO 10271. Samples of 10 high‐noble and noble gold‐based dental alloys were subjected to: (i) static immersion tests with subsequent analysis of ion release for eight different elements using mass spectrometry; (ii) electrochemical tests, including open‐circuit potential and potentiodynamic scans; and (iii) scanning electron microscopy, followed by energy‐dispersive X‐ray microscopy. The results were analyzed using one‐way ANOVA and Sidak multiple‐comparisons post‐hoc test at a level of significance of α = 0.05. Significant differences were found among the 10 alloys studied for all ions ( P < 0.001). The potentiodynamic analysis showed values from −82.5 to 102.8 mV for the open‐circuit potential and from 566.7 to 1367.5 mV for the breakdown potential. Both the open‐circuit and the breakdown potential varied considerably among these alloys. Scanning electron microscopy analysis confirmed the existence of typically small‐diameter corrosion defects, whilst the energy‐dispersive X‐ray analysis found no significant alteration in the elemental composition of the alloys. The results of this study reveal the variability in the corrosive resistance among the materials used for retention elements in prosthodontics.